1998
DOI: 10.1016/s0006-3495(98)74006-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of an Eight-State Mechanism of Cotransport to a Six-State Model Using a New Computer Program

Abstract: A computer program was developed to allow easy derivation of steady-state velocity and binding equations for multireactant mechanisms including or without rapid equilibrium segments. Its usefulness is illustrated by deriving the rate equation of the most general sequential iso ordered ter ter mechanism of cotransport in which two Na+ ions bind first to the carrier and mirror symmetry is assumed. It is demonstrated that this mechanism cannot be easily reduced to a previously proposed six-state model of Na+-D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…3). Our I-V relations for forward and reverse sugar transport provide strong first evidence that external Na binding and conformational change of the empty transporter between inside-and outside-facing conformations are the only significant voltage-dependent steps; 3) provided experimental evidence in support of the theoretical study of Falk et al (1998) that postulated the sodium dependence of the rate constants for the conformational changes of the empty transporter (k 16 and k 61 ) in the simple 6-state kinetic model for SGLT1; 4) provided direct information about the asymmetry in sugar specificity between forward and reverse Na/sugar transport and the affinity for phlorizin at the internal surface; and 5) demonstrated that our simple model accounts for Na/ glucose cotransporter kinetics, forward and reverse directions, at normal sodium concentrations. Finally, while SGLT1 can mediate sugar efflux, given the very low affinity for glucose at the cytosolic surface, under physiological conditions, there would be little or no sugar efflux mediated by SGLT1.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…3). Our I-V relations for forward and reverse sugar transport provide strong first evidence that external Na binding and conformational change of the empty transporter between inside-and outside-facing conformations are the only significant voltage-dependent steps; 3) provided experimental evidence in support of the theoretical study of Falk et al (1998) that postulated the sodium dependence of the rate constants for the conformational changes of the empty transporter (k 16 and k 61 ) in the simple 6-state kinetic model for SGLT1; 4) provided direct information about the asymmetry in sugar specificity between forward and reverse Na/sugar transport and the affinity for phlorizin at the internal surface; and 5) demonstrated that our simple model accounts for Na/ glucose cotransporter kinetics, forward and reverse directions, at normal sodium concentrations. Finally, while SGLT1 can mediate sugar efflux, given the very low affinity for glucose at the cytosolic surface, under physiological conditions, there would be little or no sugar efflux mediated by SGLT1.…”
Section: Discussionsupporting
confidence: 52%
“…6). This one-step approximation at high external [Na + ] is supported by the observation of high co-operativity between the two Na + binding sites (Parent et al, 1992b;Falk et al, 1998;Mackenzie et al, 1998;Meinild et al, 2002). However, at low external Na + concentrations, the model fails to account for the presteady-state kinetics (Hazama et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations